Carbon Nanofibers: Bionanofiber Assisted Decoration of Few‐Layered MoSe2 Nanosheets on 3D Conductive Networks for Efficient Hydrogen Evolution (Small 7/2017). Issue 7 (February 2017) - Lai, Feili; Yong, Dingyu; Ning, Xueliang; Pan, Bicai; Miao, Yue‐E; Liu, Tianxi
Abstract : In article number 1602866, Yue‐E Miao, Tianxi Liu, and co‐workers use bacterial cellulose‐derived carbon nanofibers to successfully assist with the uniform growth of few‐layered MoSe2 nanosheets. This is beneficial to synergistically achieve structural and electronic modulations for MoSe2 ‐based hydrogen evolution reaction catalysts.